Acute elbow trauma : fractures and dislocation injuries - Berner, Arne 1978- (Strategies in fracture treatments / editors, Peter Biberthaler, James P. Waddell, 2019)
This volume focuses on acute trauma to the adult elbow, including fractures, dislocations, tendon ruptures, and vascular and nerve injuries. Each chapter addresses anatomical key features, surgical and conservative therapeutic procedures, postoperative regimes and complication strategies. International elbow experts explore a range of surgical approaches, the usage of modern implants, advances in surgical techniques, and pearls and pitfalls for each trauma entity. Moreover, the authors describe total elbow arthroplasty and radial head replacement in detail, outline current clinical outcomes, and provide recommendations for therapeutic approaches and salvage measures. The book enables the orthopedic surgeon to deal with the entire spectrum of acute simple and complex elbow injuries in adults.